2003
DOI: 10.1007/s00402-003-0548-2
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results and quantitative comparison of postoperative shoulder function in traumatic and non-traumatic rotator cuff tears

Abstract: The results demonstrate that surgical reconstruction of traumatic and non-traumatic rotator cuff tears is a successful procedure. Comparison of both groups revealed significantly better postoperative results in the younger, traumatic collective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 20 publications
3
54
0
2
Order By: Relevance
“…Very little work has been done in this regard. Braune et al 12 in 2003 had stated traumatic tears to have a better outcome than the degenerative tears.…”
Section: Discussionmentioning
confidence: 99%
“…Very little work has been done in this regard. Braune et al 12 in 2003 had stated traumatic tears to have a better outcome than the degenerative tears.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the outcome of conservative treatment is hard to predict and the tear tends to increase in size with the passage of time [5]. Some authors have found better results from surgery in patients with an acute tear than in patients with a degenerative RCL [6].…”
Section: Introductionmentioning
confidence: 97%
“…Another recent study by Braune et al found better postoperative results in patients with acute tears than in patients with degenerative RCLs [6].…”
mentioning
confidence: 99%
“…Unfortunately, a perfect study could not be designed to assess the traumatic cuff tears due to intrinsic factors (degenerative process). In that report, the patients under 59 years were included, and in other report, 1) cases under 49 years were included. However, we could not exclude the degenerative pathogenesis for the cases under 49 or 59 years.…”
Section: -7)mentioning
confidence: 99%
“…1,2) Traumatic subscapularis tears were reported more than traumatic supraspinatus tears. 3,4) However, there are few reports assessing the radiological determination of traumatic rotator cuff tears.…”
mentioning
confidence: 99%